2013
DOI: 10.7567/jjap.52.06gj06
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Residual Layer Creation in Ultraviolet Nanoimprint Using Spin Coat Films for Sub-100-nm Patterns with Various Pattern Densities

Abstract: In the case of spin coat films, the variation in residual layer thickness (RLT) caused by the variation in pattern density is a problem encountered in UV nanoimprint lithography (NIL). To solve this problem, we proposed the use of capacity-equalized molds in which pattern depths are modified to equalize pattern capacity per unit area at any location. Although the effectiveness of these molds was validated using molds with various pattern sizes of the order of hundreds of micrometers, the dimensions in those ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A problem with UV-NIL is that an extra resin layer called the residual layer (RL) [3][4][5][6] is generated between the curable resin pattern and the substrate. This RL must be removed before the dry etching process, so a thin or nonexistent RL is desirable in the UV-NIL process.…”
Section: Introductionmentioning
confidence: 99%
“…A problem with UV-NIL is that an extra resin layer called the residual layer (RL) [3][4][5][6] is generated between the curable resin pattern and the substrate. This RL must be removed before the dry etching process, so a thin or nonexistent RL is desirable in the UV-NIL process.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the rapid bubble-free filling of mold pattern cavities with dimensions ranging from several tens of nanometers (45 nm half-pitch) to several hundreds of micrometers can be accomplished by using PFP as the environmental gas in UV-NIL and PAK-01 resin (Toyo Gosei). [17][18][19][20] A PFP atmosphere is not only a potential means of achieving quick and bubble-free cavity filling, but also has benefits such as decreasing the viscosity of the UV-curable resin, 18) decreasing the amount of resin that sticks to the mold during demolding, 19) and lowering demolding forces to approximately one-third of that performed in air. 20) However, the global warming potential (GWP) of PFP of 1030 may prevent its industrial use because of environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to pattern density, the residual layer thickness is not always uniform. To solve this problem, the authors proposed the volute uniform mold of the pattern cavity and demonstrated its performance in UV nanoimprint lithography [9]. 3) Smooth demolding To prevent adhesion between the UV curable polymer and the mold, the mold surface is coated with an anti-sticking layer.…”
Section: ) Bubble Defects and Their Eliminationmentioning
confidence: 99%